USING BIG DATA IN BUSINESS MANAGEMENT - Gurgu, Elena; Iatagan, Mariana; Zorzoliu, Raluca (Annals of Spiru Haret University. Economic Series, 2022)
Digitalization is fundamentally changing companies and other organizations, just as the business world has never seen before. Changes also take place on the financial and accounting side of a company. Future digital advancements are a necessity because providers use this type of systems. The use of new technologies in business management is expected especially in terms of document recognition, data exchange, receipt and payment transactions, communication, excel replacement, text recognition. Big Data is becoming an indispensable resource for many organizations. Digitalization is fundamentally changing companies and other organizations, just as the business world has never seen before. The term Big Data has evolved in a flash to take into account the rapidly expanding quantities of digital information systems that are generated, the hard work of creating that information that can be analyzed, and the actual use of that data as capital to increase efficiency, create and enable innovation, and improve decision-making.